Chronic browsing by an introduced mammalian herbivore in a tropical island alters species composition and functional traits of forest understory plant communities. (17th August 2022) - Anujan, Krishna; Ratnam, Jayashree; Sankaran, Mahesh
Abstract: Mammalian herbivores have large‐scale impacts on vegetation, altering structure, and species composition, especially in tropical grasslands and savannas. However, there is limited understanding of the potential impacts of mammalian herbivores in tropical wet forests, where they are typically less abundant. We investigated the effects of an introduced mammalian herbivore chital ( Axis axis ) on vegetation structure, composition and leaf functional traits of tropical evergreen forests of the Andaman Islands, India. Across seven islands, representing a gradient of herbivore densities, increasing chital presence was associated with decreased understory richness, understory density and adult tree richness, but was not related to adult tree density or size class distributions. We also found a significant decrease in community level leaf palatability traits (specific leaf area decreased and leaf thickness increased) with increasing chital habitat use. This community level shift in leaf trait values was better explained by intraspecific variation in leaf traits across islands rather than changes in species composition. In summary, we show persistent long‐term impacts of an introduced mammalian herbivore on understory tropical tree communities although there is little impact on adult tree communities. Our results also show that functional traits of species can be altered in response to novel herbivory, even at herbivore densities where there are no detectable impacts on adult forest structure or composition. Such altered functional traits may potentially alter ecosystem functioning in these forests even without changes in vegetation structure. Abstract in Hindi is available with online material. Abstract : Introduced mammalian herbivores can alter ecosystem structure and functioning, but their effect on tropical forests is less understood. We show that understory plant community structure is altered along a gradient of introduced deer densities across a tropical island system with naive vegetation. We also show that leaf functional traits in the understory can have persistent long‐term impacts even at deer densities at which there is little impact on adult tree communities. RESUMO: घास के मैदानों और सवाना में शाकाहारी स्तनधारी जीवों का वनस्पति प्रजातियों और संरचना पर बड़े पैमाने पर प्रभाव पड़ता है। हालांकि, उष्णकटिबंधीय सदाबहार वनों में शाकाहारी स्तनधारी जीवों के संभावित प्रभावों की सीमित समझ है। हमने भारत के अंडमान द्वीप समूह में, सदाबहार वनों की वनस्पति संरचना और पत्ती के लक्षणों पर एक द्वीप समूह के बाहर से लायी हुई शाकाहारी, चीतल (ऍक्सिस ऍक्सिस) के प्रभावों की जांच की। सात द्वीपों में, चीतल की उपस्थिति पौधों और वृक्षों की समृद्धता, और पौधों की घनत्व की कमी से जुड़ी थी, लेकिन बृक्षों की घनत्व या उनके आकार (गोलाई) के वितरण से संबंधित नहीं थी। हमने चीतल के बढ़ते उपस्थिति के साथ पत्तों के स्वाद से जुड़े कार्यात्मक लक्षणों में उल्लेखनीय कमी (पत्ती क्षेत्र और वजन का अनुपात में कमी और पत्ती की मोटाई में वृद्धि) समुदाय‐स्तर पर पाई। पत्तों के कार्यात्मक लक्षणों में यह समुदाय‐स्तरीय बदलाव, प्रजातियों की संरचना में परिवर्तन से नहीं बल्कि प्रत्येक द्वीपों में उपस्थित समान प्रजातियों के पत्तों के लक्षणों में भिन्नता से जुडी थी। संक्षेप में, इस अन्वेषण से स्पष्ट हुआ कि उष्णकटिबंधीय वन में वनस्पति समुदायों पर एक बाहर से लायी हुई शाकाहारी का लगातार दीर्घकालिक प्रभाव पड सकता है, हालांकि वयस्क वृक्ष समुदायों पर बहुत कम प्रभाव पड़ता है। हमारे परिणाम यह भी दिखाते हैं कि प्रजातियों के कार्यात्मक लक्षणों पर एक बाहर से लायी हुई शाकाहारी जानवर का असर हो सकता है, यहां तक कि जब उस जानवर की संख्या कम हो। पत्तों के लक्षण में परिवर्तन वनस्पति संरचना में बदलाव के बिना भी इन जंगलों के पारिस्थिति की तंत्र को संभावित रूप से बदल सकते हैं।.